Über die Verteilung die gaussischen Primzahlen - Vaitkevičius, J. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Вайткявичус. О взаимном расположении простых гауссовых чисел на плоскостиJ. Vaitkevičius. Apie Gauso pirminių skaičių tarpusavio išsidėstymą plokštumoje